High-Energy Phosphates and Ischemic Heart Disease: From Bench to Bedside - Yi-Dan, Hao; Ying-Xin, Zhao; Shi-Wei, Yang; Yu-Jie, Zhou (Frontiers in Cardiovascular Medicine, 2021)
The purpose of this review is to bridge the gap between clinical and basic research through providing a comprehensive and concise description of the cellular and molecular aspects of cardioprotective mechanisms and a critical evaluation of the clinical evidence of high-energy phosphates (HEPs) in ischemic heart disease (IHD). According to the well-documented physiological, pathophysiological and pharmacological properties of HEPs, exogenous creatine phosphate (CrP) may be considered as an ideal metabolic regulator. It plays cardioprotection roles from upstream to downstream of myocardial ischemia through multiple complex mechanisms, including but not limited to replenishment of cellular energy. Although exogenous CrP administration has not been shown to improve long-term survival, the beneficial effects on multiple secondary but important outcomes and short-term survival are concordant with its pathophysiological and pharmacological effects. There is urgent need for high-quality multicentre RCTs to confirm long-term survival improvement in the future.